Homoerotic Countertransference in Psychoanalytic Literature: A Thematic Analysis - Tuson, Jane (Auckland University of Technology, 2013)
This dissertation poses the question ‘how is homoerotic countertransference written about in psychoanalytic literature?’ Utilising a thematic analysis methodology, an analysis of the literature was undertaken with the aim of identifying the embedded themes within the literature. Four themes were revealed: desire; fear; taboo and acceptance. Desire was the central theme from which all the others emanated. It underpinned the writing in various guises. Fear predominantly related to the clinician’s intrapsychic response to homoerotic desire. Taboo encompassed all references to external judgment from a perceived authority or the potential opprobrium from the profession. It also related to socio-cultural attitudes to same sex attraction that are both implicit and explicit in the literature. A fourth theme of acceptance was identified. This emanated from writing that acknowledged the potency and enrichment borne out of embracing and accepting homoerotic countertransference. The implications for clinical practice of these four themes are discussed including the value of acknowledging and utilising homoerotic countertransference when it emerges in the work.
Keywords: Homoerotic; Countertransference; Thematic analysis